2023
DOI: 10.3390/diagnostics13091545
|View full text |Cite
|
Sign up to set email alerts
|

Review on the Advancements of Stethoscope Types in Chest Auscultation

Abstract: Stethoscopes were originally designed for the auscultation of a patient’s chest for the purpose of listening to lung and heart sounds. These aid medical professionals in their evaluation of the cardiovascular and respiratory systems, as well as in other applications, such as listening to bowel sounds in the gastrointestinal system or assessing for vascular bruits. Listening to internal sounds during chest auscultation aids healthcare professionals in their diagnosis of a patient’s illness. We performed an exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 94 publications
(143 reference statements)
0
5
0
Order By: Relevance
“…The authors of this article showed many benefits of remote lung auscultation, or even the sound recording itself. They also did not omit the problem related to the use of artificial intelligence to interpret the recorded auscultation phenomena, which primarily result from their possible variability [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of this article showed many benefits of remote lung auscultation, or even the sound recording itself. They also did not omit the problem related to the use of artificial intelligence to interpret the recorded auscultation phenomena, which primarily result from their possible variability [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these researchers confirmed that patients were able to perform a simple lung USG test themselves. Heldeweg et al, based on a systematic review of the literature, proved that ultrasound imaging of the lungs significantly affects clinical decision making, especially in the so-called places for quick diagnostics (e.g., emergency departments) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disease awareness is a key component for the efficient control of chronic respiratory allergies; to achieve this, a series of diagnostic and monitoring devices for home use are commercially available. The currently marked digital stethoscopes can efficiently remove non-essential noise, while they are combined with artificial intelligence (AI) algorithms that recognize, amplify, visualize, and record breath sounds such as wheezing and coughing with substantial sensitivity [61,62]. Patients or caregivers can also utilize portable digital spirometers or peak flow meters for both self-assessment and guided treatment while reviewing effort quality and, in certain cases, in a visualized, easy-to-understand form, their effort results (e.g., traffic light system) [63].…”
Section: Assessment Tools For Remote Patient Monitoringmentioning
confidence: 99%
“…3D printing technology offers the opportunities for personalization and customization, advanced functionality, and integration with modern healthcare technologies. As digital capabilities become increasingly prevalent, digital stethoscopes started gaining attraction for their improved sound quality in terms of amplification, clarity, accuracy and recordability [5].…”
Section: Introductionmentioning
confidence: 99%